Penerapan Model Pembelajaran Science, Technology, Engineering, Art, Mathematic (STEAM) untuk Meningkatkan Hasil Belajar Siswa Kelas III Madrasah Ibtidaiyah - Ema Kurniawati; Umil Muhsinin (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
In the 21st century, education is required to produce students who are creative, critical, collaborative, and communicative to face the challenges of the times. Therefore, the implementation of the STEAM learning model is one innovative solution to improve the quality of learning and student outcomes, especially in Natural and Social Sciences (IPAS) subjects. This research is Classroom Action Research (CAR) that adopts the Kemmis and McTaggart model with two learning cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The purpose of this research is to improve student learning outcomes through the implementation of the STEAM learning model. The results showed an increase in student learning outcomes from cycle I to cycle II. In the cognitive domain, the average student score increased from 76% in cycle I to 88% in cycle II. In the psychomotor domain, there was an increase from 71% in cycle I to 91% in cycle II. Meanwhile, in the affective domain, student activities increased from 78% in cycle I to 92% in cycle II. Based on the results of the study, the implementation of the STEAM learning model can be declared effective in improving student learning outcomes in IPAS subjects for grade III students of Madrasah Ibtidaiyah Al-Munawwarah, Jambi City.